Towards Integrated Smart Tourism Systems in Urban Destinations: A Systematic Literature Review on End-to-End Journey and SME Digital Integration - Veza, Okta; Arifin, Nofri Yudi; Agustini, Sherly (YCMM, 2026)
The rapid development of digital technologies has significantly transformed the tourism sector, particularly in urban destinations characterized by complex ecosystems and diverse stakeholders. Smart tourism systems have emerged as a key approach to enhancing service efficiency, improving tourist experiences, and enabling data-driven decision-making. However, existing studies are still fragmented and largely focus on partial implementations, lacking comprehensive end-to-end integration. This study aims to conduct a systematic literature review on smart tourism systems in urban destinations, with a focus on system integration, end-to-end tourist journey, and Small and Medium Enterprises (SMEs) digital integration. The review was conducted using selected articles from reputable international journals published between 2023 and 2025. The analysis categorizes the studies into three groups: same system and same scope, same system and similar scope, and same system and different scope. The results indicate that only a limited number of studies have developed fully integrated smart tourism systems, while most studies focus on specific components or are applied in different domains. In addition, stakeholder integration and SME digital inclusion remain key challenges in developing comprehensive smart tourism ecosystems. This study contributes by identifying research gaps and proposing future research directions focused on developing integrated, scalable, and inclusive smart tourism systems. The findings are expected to support the advancement of smart tourism system design in urban destinations.